Whole-Virion Influenza Vaccine Recalls an Early Burst of High-Affinity Memory B Cell Response through TLR Signaling - Onodera, Taishi; Hosono, Akira; Odagiri, Takato; Tashiro, Masato; Kaminogawa, Shuichi; Okuno, Yoshinobu; Kurosaki, Tomohiro; Ato, Manabu; Kobayashi, Kazuo; Takahashi, Yoshimasa (The Journal of immunology (1950), 2016)
Inactivated influenza vaccines have two formulations, whole- and split-virion types; however, how differential formulations impact their booster effects remain unknown. In this study, we demonstrate that whole-virion vaccines recall two waves of Ab responses, early T cell–independent (TI) and late T cell–dependent responses, whereas split-virion vaccines elicit the late T cell–dependent response only. Notably, higher-affinity Abs with improved neutralizing activity are provided from the early TI response, which emphasizes the important contribution of the formulation-dependent response in the protective immunity. Moreover, we show that the early TI response completely requires B cell–intrinsic TLR7 signaling, which can be delivered through viral RNAs within whole-virion vaccine. Thus, our results indicate that TLR agonists in whole-virion type improve recall Ab responses by directly targeting memory B cells, a finding with important implications for vaccine strategies aimed at the prompt recall of high-affinity neutralizing Abs.